Specialised lexicography: lemmas for a dictionary of graphics engineering - Esandi-Baztan, M. ª Ángeles (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The specialised lexicography of engineering graphics does not have a reference work that provides, by means of occasional queries, assistance of technical application and knowledge acquisition of engineering graphic expression (EGE) to students in a university context. A lexicographical work on EGE includes specialised lexicographical units whose full meaning is given in two components: one verbal and one graphic. This work suggests a procedure that provides lexicographers with an initial list of specialised units of meaning in this field that can satisfy the information needs of a dictionary potential user and comprises a reference work of EGI. This first list of lemmas is obtained using the Delphi method and will serve as a basis for a future Spanish dictionary in the field of engineering graphics. We present a process that consists of two rounds of experts with their respective questionnaires plus a consultation addressed to the students. It is adopted a method of expert endorsed by experts, as well in this case, an expert designs the first questionnaire that is sent to a group of experts. It should be noted that additionally the first round has, prior to the dynamics established in this method, the aim of identifying of specialised units by the expert panel. The concepts obtained are considered fundamental at the teachers’ discretion, because of the difficulty they represent, their importance within the field of knowledge or because they are the most prevalent misconceptions in the learning context referred to in this work. The additional information provided by the students allows for an interesting discussion on 52 concepts and the comparison of the results with the experts’ opinion. Once the concepts have been identified and agreed upon, we consider the theoretical implications of the theory of lexicographic functions (TFL) in order to define a practical application of this work.